COPD-related Bronchiectasis; Independent Impact on Disease Course and Outcomes. (1st December 2014) - Gatheral, Timothy; Kumar, Neelam; Sansom, Ben; Lai, Dilys; Nair, Arjun; Vlahos, Ioannis; Baker, Emma H.
Abstract Background: COPD and radiographic bronchiectasis frequently coexist but the effect of this on the clinical course of COPD is not fully understood. We determined the impact of bronchiectasis on clinical outcomes in COPD patients, independent of coexisting emphysema and bronchial wall thickening (BWT). Methods: COPD patients admitted with first exacerbation 1998–2008 were identified retrospectively using ICD10 codes J44.0, 1, 8, 9. Patients with suitable CT scans were graded for severity of bronchiectasis, emphysema and BWT on a 5 point scale (0-absent, 1-minor, 2-mild, 3-moderate, 4-severe). Results: 406 patients (71 ± 11 years, 56% male, FEV1 52 ± 23% predicted) were included; 278 (69%) patients had bronchiectasis: minor, 112 (40%); mild, 81 (29%); moderate, 62 (22%); severe 23 (8%). Bronchiectasis severity correlated with severity of BWT (p < 0.001) but not emphysema (p = 0.090). Bronchiectasis independently determined sputum isolation of Pseudomonas aeruginosa (Odds ratio (OR) 1.39 (95% CI 1.07 to 1.80), p = 0.013) and atypical mycobacteria (OR 2.44 (95% CI 1.04 to 5.69), p = 0.040), annual respiratory admissions (p = 0.044) and inpatient days (p < 0.001), but did not predict survival (p = 0.256). Conclusions: Radiographic bronchiectasis in COPD patients is associated with increased respiratory infection and hospitalisation, independent of coexisting emphysema and BWT. COPD-related bronchiectasis is therefore an important diagnosis with potential implications for treatment.